Étude Comparative de L'emploi du Style indirect libre dans l'œuvre romanesque de Flaubert et D'Austen. (2nd January 2016) - Russell, Adam
Abstract : Gustave Flaubert and Jane Austen died at opposite ends of the nineteenth century, on opposite sides of the English Channel, and almost at opposite ends of the moral spectrum. Consequently, their novels are in many ways very different and seldom the object of comparative studies. However, given that both novelists experimented with advanced narrative techniques usually known under the umbrella term free indirect discourse (FID) or style indirect libre (SIL), this study seeks to compare the ways in which each novelist used this technique in a selection of passages from their works.